2003
DOI: 10.1093/nar/gkg324
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding by yeast Mlh1 and Pms1: implications for DNA mismatch repair

Abstract: The yeast Mlh1-Pms1 heterodimer required for mismatch repair (MMR) binds to DNA. Here we map DNA binding to N-terminal fragments of Mlh1 and Pms1. We demonstrate that Mlh1 and Pms1 N-terminal domains (NTDs) independently bind to double-stranded and single-stranded DNA, in the absence of dimerization and with different affinities. Full-length Mlh1p alone, which can homodimerize, also binds to DNA. Substituting conserved positively charged amino acids in Mlh1 produces mutator phenotypes in a haploid yeast strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
78
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 42 publications
7
78
0
Order By: Relevance
“…Unlike other ND10 proteins that play antiviral roles, MLH1 is required for viral gene expression, and viral growth is inhibited when MLH1 is depleted. MLH1 may bind the incoming viral genome directly, as MLH1 has some affinity for both double-and single-stranded DNA (19). Alternatively, it may associate with viral genomes indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other ND10 proteins that play antiviral roles, MLH1 is required for viral gene expression, and viral growth is inhibited when MLH1 is depleted. MLH1 may bind the incoming viral genome directly, as MLH1 has some affinity for both double-and single-stranded DNA (19). Alternatively, it may associate with viral genomes indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…We note that a similar conclusion has been reached for representative eukaryotic MutL homologues. In yeast it has been shown that point mutations in PMS1 (Pms1-K328E) and MLH1 (Mlh1-R273E,R274E), located within a proposed DNA binding groove, increase the mutation frequencies and rates in vivo (41). These proteins also fail to bind DNA in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pms1-G882E and pms1-H888 mutations had no detectable effect on Pms1 stability or interaction with Mlh1 as determined with the two-hybrid assay. The Cterminal domain of MutL has been shown to be important for homodimerization (1,12), interactions with MutH and UvrD (25,26), and DNA binding (27). Furthermore, based on the recently solved crystal structure of the COOH-terminus of MutL (23), the residues affected by the pms1 alleles studied here appear to be in an exposed region of the protein and, therefore, may be important for interaction with other proteins and/or DNA during MMR.…”
Section: Discussionmentioning
confidence: 82%